2008
DOI: 10.1111/j.1939-165x.2008.00007.x
|View full text |Cite
|
Sign up to set email alerts
|

A multicentric retrospective study of serum/plasma urea and creatinine concentrations in dogs using univariate and multivariate decision rules to evaluate diagnostic efficiency

Abstract: Simultaneous measurement of both urea and creatinine is of limited diagnostic value over the analysis of a single variable. Creatinine is the preferred analyte as it is affected by fewer extrarenal factors of variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
2
7
0
4
Order By: Relevance
“…Differences in urea concentration were slightly more distinguishable by inspection, but may be less important than those observed for creatinine because urea is a less specific indicator of renal function. A recent study describing the influence of sources of variation on urea and serum creatinine concentrations in dogs was in agreement with our findings that breed has a significant effect on urea and creatinine values 28 . That study reported that the effect is complex and influenced by differences in other variables such as health status (controlled for in our study), age, and sex.…”
Section: Analytical Methods For Serum Biochemical Assays Used In Thisupporting
confidence: 93%
“…Differences in urea concentration were slightly more distinguishable by inspection, but may be less important than those observed for creatinine because urea is a less specific indicator of renal function. A recent study describing the influence of sources of variation on urea and serum creatinine concentrations in dogs was in agreement with our findings that breed has a significant effect on urea and creatinine values 28 . That study reported that the effect is complex and influenced by differences in other variables such as health status (controlled for in our study), age, and sex.…”
Section: Analytical Methods For Serum Biochemical Assays Used In Thisupporting
confidence: 93%
“…Serum creatinine is influenced by age and particularly by breed in dogs and, to a lesser extent, in cats . It might also be influenced by sex and the veterinary clinic evaluating the patient . Therefore, sCr would benefit from age‐ and breed‐specific reference intervals, ideally (although not practically) for every individual instrument and laboratory.…”
Section: Renal Biomarkers: Bloodmentioning
confidence: 99%
“…seleccionados 61 caninos con anamnesis, síntomas clínicos y resultados del urianálisis compatibles con Las concentraciones de urea y creatinina en afección renal, de por lo menos 2 semanas de plasma y suero son rutinariamente analizadas como duración, para determinar cronicidad, que marcadores indirectos de la tasa de filtración consultaron en el referido Hospital durante el año glomerular y se ha reportado que están altamente 2013. De cada perro se obtuvo 3 mL de sangre, correlacionadas (5,6). La medición simultánea de mediante punción de la vena cefálica, depositada en ambas es de valor diagnóstico limitado sobre el tubos, que fueron derivadas al laboratorio.…”
Section: Introductionunclassified
“…análisis de una sola variable. La creatinina es el analito preferido, al verse afectado por un menor Las muestras de suero fueron procesadas en número de factores extrarrenales de variación (6).…”
Section: Introductionunclassified
See 1 more Smart Citation